Community-based child protection with Palestinian refugees in South Lebanon: Engendering hope and safety. (September 2015) - O'Leary, Patrick; Hutchinson, Aisha; Squire, Jason
Engendering hope with refugee children is an important role of those working in child protection. This article reports on one part of an evaluation of a community-based child protection project working with Palestinian refugees in southern Lebanon. Validated tools were used to measure levels of hope in 222 children and young people before and after social work intervention. Results were compared to a smaller group of similar children who received no intervention. Children who received social work intervention were shown to have significant improvement in hope. Results highlight the need for early intervention and in some cases intensive contact.